2019
DOI: 10.2139/ssrn.3321060
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Innovative Firms Using Web Mining and Deep Learning

Abstract: Innovation is considered as a main driver of economic growth. Promoting the development of innovation through STI (science, technology and innovation) policies requires accurate indicators of innovation. Traditional indicators often lack coverage, granularity as well as timeliness and involve high data collection costs, especially when conducted at a large scale. In this paper, we propose a novel approach on how to create firm-level innovation indicators at the scale of millions of firms. We use traditional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Our results for product innovators are in line with the results of Kinne and Lenz (2019). Their statistical model has reached a similar accuracy for product innovators only observed in one MIP wave.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results for product innovators are in line with the results of Kinne and Lenz (2019). Their statistical model has reached a similar accuracy for product innovators only observed in one MIP wave.…”
Section: Discussionsupporting
confidence: 90%
“…Following the idea of web-based innovation indicators, Kinne & Lenz (2019) attempt to predict innovation at the firm level using textual information on websites and novel machine learning tools. They use traditional firm-level innovation indicators from the MIP 2017 to train an artificial neural network classification model on labelled (innovative/non-innovative) web texts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Web mining describes the application of data mining techniques to uncover relevant data characteristics and relationships (e.g., data patterns, trends, and correlations) from previously web scraped unstructured web data [19]. We do so by using data from the Mannheim Enterprise Panel (MUP) as the firm database, and then categorize web scraped firms using their website texts and conduct multivariate analyses based on firm characteristics and a deep-learning-based product innovator probability indicator [20].…”
Section: Introductionmentioning
confidence: 99%
“…The initial logistic regression model created had an accuracy of 93% and an F1-score of 93% on the test set (Daas & van der Doef, 2020). Kinne and Lenz (2019) demonstrated that the text on the websites of German companies could also be used to detect innovative companies. Their Deep Learning based model had an F1-score of 80%.…”
Section: Introductionmentioning
confidence: 99%